Interpersonal Adaptation, Self-Efficacy, and Metacognitive Skills in Italian Adolescents with Specific Learning Disorders: A Cross-Sectional Study - Elena Commodari; Valentina Lucia La Rosa; Elisabetta Sagone; Maria Luisa Indiana (MDPI AG, 2022)
This study aimed to explore interpersonal adaptation, generalized self-efficacy, and metacognitive skills in a sample of Italian adolescents with and without a specific learning disorder (SLD). A total of 564 secondary and high school students (males = 236; females = 328; age range: 11-19; M = 16.14, SD = 1.70) completed a set of standardized tests assessing social and interpersonal skills (non-affirmation, impulsiveness, narcissism, social preoccupation, and stress in social situations), general self-efficacy, and metacognition. Students with SLD reported a lower interpersonal adaptation than students without SLD. Furthermore, students with SLD were more impulsive and had more problems handling social situations. They also reported lower levels of self-efficacy but higher metacognition scores than peers without SLD. The use of compensatory tools was associated with better interpersonal skills and higher levels of self-efficacy in students with SLD. Finally, using these instruments is predictive of high levels of metacognitive skills in adolescents with SLD. In line with the previous literature, this study showed the presence of a gap between adolescents with and without an SLD in terms of interpersonal adaptation, general self-efficacy, and metacognitive skills in the school context. Further studies are needed on the psychological well-being of adolescents with SLD and especially on the protective role of personal, social, and environmental characteristics.